The performance evaluation of the promising high-stability foil bearings basing with flexure pivot tilting pads. (1st December 2019) - Lyu, Peng; Feng, Kai; Zhu, Binghui; Zhang, Kai; Sun, Dongling
Highlights: A promising high-stability foil bearing named FPTPFB is developed. A comprehensive theoretical model is built for predicting the performances of FPTPFB. The numerical iterative methods are presented. The influences of the key design parameters are analyzed. The results demonstrate that the FPTPFB have outstanding performances. Abstract: Foil bearings are prone to instability due to their inherent high cross-coupled stiffness which causes self-excited sub-synchronous instability. In this paper, three flexure pivot tilting pads are introduced into the foil bearings to reduce the cross-coupled stiffness largely, evolving into an improved bearing named flexure pivot titling pad foil bearing (FPTPFB). A comprehensive theoretical model is built for predicting the performances of FPTPFB so as to understand the interaction mechanism of the flexure pads, the foil structure and the air film. The numerical iterative method for predicting the static and dynamic performances of the bearing are presented. Both the static performances including the journal eccentricity, attitude angle, limited load and the dynamic coefficients of the bearing are compared with the traditional three lobes foil bearing (TLFB). Furthermore, the influences of the key design parameters such as pivot offset, flexure web tilting stiffness, bearing nominal clearance and preload are analyzed. The results demonstrate that the FPTPFB have the advantages of low cross-coupled stiffness, good damping, high load capacity and low machining accuracy requirements. The research can provide some guidelines both for the design and optimization of this promising new bearing.